The Kinetic Rate Law for the Autocatalytic Growth of Citrate‐Stabilized Silver Nanoparticles. Issue 6 (20th April 2015) - Kytsya, Andriy; Bazylyak, Liliya; Hrynda, Yuriy; Horechyy, Andriy; Medvedevdkikh, Yuriy
ABSTRACT The formation of sodium citrate stabilized spherical silver nanoparticles synthesized by homogeneous nucleation in aqua solutions was monitored by the method of direct potentiometry. It was observed that the kinetic curve of Ag+ ions reduction can be described by the Finke–Watzky (FW) autocatalytic two–step mechanism in the case of a large excess of hydrazine and NaOH. To expand the FW minimalistic model, the impact of the starting concentrations of the reagents on the kinetics of Ag nanoparticles synthesis was studied. It was determined that the nucleation stage is limited by the homogeneous process of ions Ag+ reduction, and the reaction orders for the all reagents are calculated. A surface–dependent model of Ag nanoparticle growth is proposed, which takes into account the change in the hydrazine and alkali concentrations; the rate constants of the pseudoelementary reactions are also calculated.